2019
DOI: 10.7867/1983-1501.2019v21n1p6-16
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Desempenho De Três Algoritmos Na Classificação De Uso Do Solo a Partir De Geotecnologias Gratuitas

Abstract: O uso de sensores remotos aliados ao Sistema de Informação Geográfica tem sido de suma importância na classificação e monitoramento do uso e ocupação do solo, permitindo obter importantes produtos que podem subsidiar o planejamento e gestão do território. Assim, este trabalho teve por objetivo avaliar o desempenho dos classificadores supervisionados Minimum Distance-MD, o Maximum Likelihood-ML e o Spectral Angle Mapping-SAM na classificação do uso do solo em uma área do sul do estado do Amazonas através do uso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…When comparing the means of each agrometeorological variable, between the harvest years and through the Z test, only rainfall in the 1aMVDD1d ten-day interval was statistically equal in the two harvest years (5% significance) (Table 1). This difference between the harvest years also occurred when the maps generated for each variable under study (Figures 6 and 7); and by similarity measures of Global Accuracy, Kappa and Tau concordance indexes (Table 2), only rainfall in the two ten-day intervals showed similarities between the harvest year maps (Duarte & Silva, 2019).…”
Section: Descriptive and Spatial Analysis Of Soybean Productivity And Agrometeorological Variablesmentioning
confidence: 69%
See 1 more Smart Citation
“…When comparing the means of each agrometeorological variable, between the harvest years and through the Z test, only rainfall in the 1aMVDD1d ten-day interval was statistically equal in the two harvest years (5% significance) (Table 1). This difference between the harvest years also occurred when the maps generated for each variable under study (Figures 6 and 7); and by similarity measures of Global Accuracy, Kappa and Tau concordance indexes (Table 2), only rainfall in the two ten-day intervals showed similarities between the harvest year maps (Duarte & Silva, 2019).…”
Section: Descriptive and Spatial Analysis Of Soybean Productivity And Agrometeorological Variablesmentioning
confidence: 69%
“…The spatial distribution of the productivity and agrometeorological variables in the state of Paraná was analyzed by comparing the maps of the two harvest years, using similarity measures of Global Accuracy (GA), Kappa (K) and Tau (T) (Duarte & Silva, 2019).…”
Section: Spatial Statisticsmentioning
confidence: 99%
“…For noise elimination and image smoothing, the Majority parameters 3 × 3 filter was applied (Vasconcelos et al, 2016). Then, the classification was edited through visual interpretation according to the spectral behavior of each pixel (Duarte & Silva, 2019). After, the file was transformed into a vector file (shapefile) and quantified, generating tabulated data.…”
Section: Study Areamentioning
confidence: 99%
“…A work of soil genesis with flooding cycles has shown that high acidity has been observed in superficial horizons in lowland soils due to ferrolysis (Barbiero et al, 2010;Coringa et al, 2012;Da Silva et al, 2019). Studies in Gleisoil under native vegetation on the banks of the Guamá River attested acid pH in water and KCl associated with the alternation between flood and ebb tide (Lopes et al, 2006).…”
Section: Classification Of the Island Soilmentioning
confidence: 99%
“…Nesse sentido, o uso do Sensoriamento Remoto tem se tornado mais frequente, posto que é um dos recursos tecnológicos mais eficaz e viável para estabelecer um estudo e controle de áreas extensas como as bacias hidrográficas, uma vez que essa ferramenta possibilita obter dados e detectar as modificações ocorridas na superfície do solo, isto é, na paisagem ao longo do tempo (DUARTE & SILVA, 2019;CHOWDHURY et al, 2020). Tais recursos tecnológicos são muito utilizados no estudo do uso e ocupação do solo, visto que possibilitam fazer um levantamento do avanço do desmatamento, da agricultura, assim como da área urbana, além de propiciarem a construção de cenários sobre os usos futuros (EL-TANTAWI et al, 2019;ULLAH et al, 2019).…”
Section: Introductionunclassified